The position of a duodenal diverticulum in the area of the major duodenal papilla and its potential clinical implications - E. Jakubczyk; M. Pazurek; A. Mokrowiecka; B. Woźniak; E. Małecka-Panas; M. Podgórski; M. Polguj; M. Topol (Folia Morphologica, 2021)
BACKGROUND: Although duodenal diverticula are associated with less frequent pathology than the colonic diverticula in the large intestine, their periampullary position may have significant clinical implications. The aim of the study was to identify any possible correlation between the type of localisation of the major duodenal papilla, duodenal diverticula, and some particular clinical issues. MATERIALS AND METHODS: In total, 628 patients (408 females and 220 males; aged 21–91 years), who underwent endoscopic retrograde cholangiopancreatography were included in this study. The patients were divided into two groups: a study group comprising 66 (10.5%) patients with periampullary position of diverticula (group A), and a control group comprising 562 (89.5%) patients without diverticula (group B). RESULTS: A duodenal diverticulum was diagnosed in the periampullary position in 66/628 (10.5%) patients: 41 women (aged 52–91 years) and 25 men (aged 54–83 years). CONCLUSIONS: Three types of localisation were observed for the major duodenal papilla with regard to the diverticula, with the most common type being next to each other (type III). In patients with diverticula, similar frequencies of gallstone occurrence are observed in men and women. Patients with papilla in the diverticulum who underwent cholecystectomy are more prone to develop lithiasis.